TRANSLATING FORMAL TEXTS AND ITS STRATEGIES AMONG COMPANY EMPLOYEES AS EFL ADULT LEARNERS - Catur Wijayanti; Akhmad Baihaqi (Cakrawala Pedagogik, 2023)
This present study aims to investigate how the EFL adult learners use translation strategies to overcome the problems in translating and understanding the formal documents. The method was case study. The participants were five employees from CV Biru Langit Lestari. The company is located in Serang, Banten Province, Indonesia. The data collecting technique was observation and interview. The data analysis, meanwhile, used the Miles and Huberman Model. This study reveals that the translation strategies may help the learners to overcome the problems in understanding the formal documents. They use Google Translate as MT only as the preliminary process in translation. They choose both direct and indirect strategies in understanding and translating the documents. They used both borrowing and literal for direct strategies, then transposition and adaptation for indirect strategies.